From visiting phenomenon to the culture of name: The case of the tomb of fatih ahmed baba - Özbolat, Abdullah (Ankara Haci Bayram Veli University, 2013)
Subject of this study is the relationship between visiting phenomenon and culture of name. In the case of Tomb of Fatih Ahmed Baba in Elazig/Harput, a reflection of the culture of the name from visiting phenomenon was observed. The children born after visiting the shrine were given the name of entombed saint as a sign of gratitude and thanksgiving. The fact that the name Fethi Ahmet is widespread in Elazi? is associated with the Tomb of Fatih Ahmed Baba in Elazig/Harput. When tombs are considered to be expert at wishes, Tomb of Fatih Ahmed Baba can be seen as an expert at giving sons and also the children who are desired to survive. The sample of the study consists of people called Ahmet Fethi, Fatih Ahmet, Fetih Ahmet and Fethi Ahmet due to the tomb of Fatih Ahmed Baba. The sample group of 60 people was reached through the snowball technique. The age range of the sample group was identified as 18-53. In this study, qualitative methods were utilized and the data were obtained with interview technique. Based on the findings of the fieldwork, reflection of the culture of the name from visiting phenomenon was conceptualized in eight dimensions. These are the dimensions of benefiting an agent, medical incurability, gender, attribution of spiritual direction, sustaining the name-character, dream motive, Alawism-Sunnism and rationalism-secularism. In the case of Tomb of Fatih Ahmed Baba, having a child, especially a son and survival of the born children appear to be of holiness. This study tries to investigate the factual reality of wishes and vows depending on the data collected from fieldwork in the case of tomb of Fatih Ahmet Baba.
Ziyaret fenomeninden isim kültürüne: fatih ahmet baba türbesi örne?i
Keywords: Culture of name; Elazig; Identity; Tomb; Visiting phenomenon